Situation Report: Poland, 27 February 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Results of Rapacki's Visit to Great Britain Communist Preparatory Commission Ends Warsaw Meeting Change in Leadership of Socialist Youth Union Polish-Japanese Trade to Increase Poland and Comecon